Recent trends in union finance; a critique of the budgetary policy of the Government of India since 1935 - Mukherji, Sarit Kumar. [from old catalog] (Calcutta : Bookland, 1964)
This book is a thoroughly revised version of 'the Budgetary policy of the Government of India Since 1935'. The book is an objective analysis of the financial policy and is meant for discerning readers
Includes index
Includes bibliographic references
osc 21/05/2018
Loans
Keywords: Finance, Public